Incarnatorische theologie: Dogmatiek op zoek naar een nieuw motief - Erp, Stephan van (Tijdschrift voor theologie, 2011)
Since Edward Schillebeeckx started this journal fifty years ago, modern theology has experienced rise and ruin. In his opening article of 1961, he was one of the first to put into words what the new challenges were for modern theology. According to him, the ever-new present offered the dynamic material for theology. The discovery of the historical, in its different forms of the past, the present and the future, gave an impetus to new theologies that have proven to be very influential since then. The concept of the historical gave rise to a new connection between anthropology and Christology. Furthermore, an awareness of context and the social position of the theologian led to the development of a communicative theology that reshaped itself after the audience it was addressing its work to. Contextual theologies emerged which are further developed into a theology of recontextualisation (Boeve) and a theology of culture (Borgman). A reaction against these new anthropological and contextual developments was the emergence of neo-orthodox and retraditionalisation theologies, currently very influential, like Barthian theologies and John Milbank’s Radical Orthodoxy. In this article, the author proposes a new motif for dogmatic theology, namely incarnation in its historical and eschatological form. The author argues that in the end, neither critical reasoning, nor hermeneutics (either contextual, biblical or ecclesial), nor tradition should be the starting points of dogmatic theology, but the ongoing historical revelation of God in Jesus Christ who is present ever anew in the time and space that people live in today. Building on the work of Schilllebeeckx, and of contemporary theologians such as Rowan Williams and Oliver Davies, he outlines a dogmatic theology that is rooted in a community in which incarnation is historically present, constituting a future that is God’s future in this world.